Thermodynamic description of the plutonium – α–d–isosaccharinic acid system ii: Formation of quaternary Ca(II)–Pu(IV)–OH–ISA complexes. (November 2018) - Tasi, A.; Gaona, X.; Fellhauer, D.; Böttle, M.; Rothe, J.; Dardenne, K.; Polly, R.; Grivé, M.; Colàs, E.; Bruno, J.; Källstrom, K.; Altmaier, M.; et al.
Abstract: The quaternary system Ca(II)–Pu(III/IV)–OH–ISA was investigated in a series of solubility experiments where equilibrium conditions were reached from undersaturation conditions with PuO2 (ncr, hyd) at T = (22 ± 2) °C under Ar atmosphere. Experiments were performed in 0.1 m NaCl–NaOH–NaISA–CaCl2 solutions at 8 ≤ pHm  ≤ 12.5 (pHm  = –log [H + ], in molal units), 10 −5  m ≤ m(ISA)tot  ≤ 10 −2  m and 10 −3.5  m ≤ m(Ca)tot  ≤ 0.02 m. Reducing conditions were adjusted and buffered with hydroquinone (HQ) or Sn(II), which allowed us to work in the (pe + pHm ) region ≈ 9 and ≈ 1.5, respectively. Solid phase characterization ( in-situ XRD, XANES and EXAFS) and analogy with the ternary system Pu–OH–ISA previously studied by our group indicate that PuO2 (ncr, hyd) remains unaltered in the course of the solubility experiments at pHm  ≤ 12 and controls the solubility of Pu under reducing conditions in the presence of ISA and Ca(II). In HQ-systems, the impact of ISA on the solubility of PuO2 (ncr, hyd) is clearly enhanced compared to Ca(II)-free solutions of analogous composition, thus indicating the formation of quaternary complexes of the type Ca(II)–Pu(IV)–OH–ISA in the aqueous phase. The combination of slope analysis of the solubility data and DFT calculations support the predominance of the two aqueous quaternary complexes Ca(II)Pu(IV)(OH)3 ISA–H + and Ca(II)Pu(IV)(OH)3 ISA–2H (aq) below and above pHm  ≈ 11, respectively. The same speciation scheme explains properly the solubility of Pu in Sn(II)-buffered systems at pHm  > 11. Below this pHm, solubility data under these very reducing conditions suggest the possible formation of ternary Pu(III)–OH–ISA aqueous complexes, although the scatter of the data does not allow a definitive conclusion to be drawn. The presence of Ca(II) in solution destabilizes Pu–ISA colloids, which significantly enhance Pu solubility in comparable, Ca-free systems. Based on these experimental and theoretical results, a thermodynamic model for the system Ca 2+ –Pu 4+ –OH – –Cl – –ISA – –H2 O(l) is derived. This study provides quantitative tools to evaluate the solubility behavior of Pu in reducing cementitious environments containing ISA, as expected in underground repositories for low- and intermediate-level radioactive waste (L/ILW) due to the degradation of cellulosic materials. Highlights: The presence of Ca(II) and ISA increases Pu solubility up to 2.5 log10 -units. Formation of Ca(II)–Pu(IV)–OH–ISA complexes confirmed in alkaline, reducing systems. Ca(II) ions contribute to the agglomeration of "Pu–ISA" colloids. DFT provides relevant insights on the structures of Ca(II)–Pu(IV)–OH–ISA complexes. A thermodynamic model is derived for the system Ca 2+ –Pu 4+ –OH – –Cl – –ISA – –H2 O(l).